A comparison of noise mapping data and people's assessment of annoyance: How can noise action plans be improved?. (August 2018) - Felcyn, Jan; Preis, Anna; Kokowski, Piotr; Gałuszka, Michał
Highlights: Traditional ICBEN scales could be replaced with a simple dichotomic question. Information from noise maps should be enriched by noise annoyance surveys' results. People are more sensitive to noise during sleep than they are in the daytime. Abstract: In this paper the results of noise maps counted for cars and trams, in 10 areas in the city of Poznań, are analyzed in the context of possible action plans. These results are compared with the information from surveys, involving 794 participants, performed at the same 10 areas. The general results showed that basing solely on the values of noise indicators, i.e. information from the noise maps, is not sufficient for reliable planning of noise action plans, particularly those created in response to multiple noise sources. The exceedance of a noise limit for a given sound source does not necessarily mean that this source is the most annoying for inhabitants. To find a solution to this problem, we propose conducting dedicated noise surveys in the specific areas in each city (in which the noise maps are calculated) where we know a priori that more than one noise source will occur at the same time and could be potentially annoying. In the proposed survey we suggest using two specified questions: whether a given sound source is annoying or not, and which sound source should be the first one to be eliminated, if this is possible. This new survey proposal is the result of an analysis of the survey performed within this study. Some methodological changes are proposed with regard to the survey that was actually used. This new approach could improve decisions about action plans and provide more complex information about peoples' assessment of noise annoyance evoked by different sound sources.